2020
DOI: 10.31489/2020no2/6-10
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Magnetic Properties of Ferrites During Radiation-Thermal Sintering

Abstract: The results of a comparative analysis of the laws governing the formation of ferrite hysteresis loop parameters sintered in thermal and radiation-thermal conditions were shown. The influence of radiation exposure on the interconversion of microstructure defects and their content in ferrites, depending on the duration and temperature of treatment, was established. Also, it was shown that recrystallization grain growth under irradiation conditions is ahead of grain growth during thermal heating. The observed rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A fundamental phenomenon of a multiple increase in the speed of multicomponent powder synthesis [11][12][13][14] and sintering of compacts [15][16][17][18][19] induced by radiation-thermal mode was discovered. Sintering of lithiumtitanium ferrites under specific conditions of a combined effect of high temperatures and intense electron fluxesis the most well studied process [20][21][22]. The patterns of ferrite compaction were revealed, and a multiple increase in the compaction rate of lithium-titanium ferrites under these sintering conditions was shown [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental phenomenon of a multiple increase in the speed of multicomponent powder synthesis [11][12][13][14] and sintering of compacts [15][16][17][18][19] induced by radiation-thermal mode was discovered. Sintering of lithiumtitanium ferrites under specific conditions of a combined effect of high temperatures and intense electron fluxesis the most well studied process [20][21][22]. The patterns of ferrite compaction were revealed, and a multiple increase in the compaction rate of lithium-titanium ferrites under these sintering conditions was shown [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of fast electron exchange, regardless of the type of representation of the crystal chemical formula of the studied oxide, it contains trivalent iron ions in the tetrahedral (A) position , trivalent iron ions in the octahedral (B) position , as well as ions with intermediate valence in the octahedral position ), participating in the Verwey mechanism of electron exchange [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The stability of nanoparticles is determined by the amount of weight loss, as well as the crystallinity degree (degree of structural ordering), which should not exceed 10% of the initial values. At the same time, several previous studies have shown that the processes of corrosion and degradation of nanoparticles have a pronounced dependence on the phase composition of nanoparticles, as well as the structural ordering degree [11,19].…”
Section: Corrosion Resistance Testsmentioning
confidence: 93%